Lack of Functional Trehalase Activity in Candida parapsilosis Increases Susceptibility to Itraconazole - Ruth Sánchez-Fresneda; María Luz Muñoz-Megías; Genoveva Yagüe; Francisco Solano; Sergi Maicas; Juan Carlos Argüelles (Journal of Fungi, 2022)
Central metabolic pathways may play a major role in the virulence of pathogenic fungi. Here, we have investigated the susceptibility of a Candida parapsilosis mutant deficient in trehalase activity (atc1Δ/ntc1Δ strain) to the azolic compounds fluconazole and itraconazole. A time-course exposure to itraconazole but not fluconazole induced a significant degree of cell killing in mutant cells compared to the parental strain. Flow cytometry determinations indicated that itraconazole was able to induce a marked production of endogenous ROS together with a simultaneous increase in membrane potential, these effects being irrelevant after fluconazole addition. Furthermore, only itraconazole induced a significant synthesis of endogenous trehalose. The recorded impaired capacity of mutant cells to produce structured biofilms was further increased in the presence of both azoles, with itraconazole being more effective than fluconazole. Our results in the opportunistic pathogen yeast C. parapsilosis reinforce the study of trehalose metabolism as an attractive therapeutic target and allow extending the hypothesis that the generation of internal oxidative stress may be a component of the antifungal action exerted by the compounds currently available in medical practice.